Umbilical Cord Blood Adiponectin, Leptin, Insulin, and Ghrelin in Premature Infants and Their Association With Birth Outcomes - Han, Luyan; Li, Bo; Xu, Xiaojing; Liu, Shufang; Li, Zhenghong; Li, Ming; Wang, Danhua (Frontiers in Endocrinology, 2021)
Background: Premature/low birth weight infants are at significantly higher risk of metabolic diseases in adulthood, which may be related to fetal adipokine levels. We aimed to investigate the differences of the umbilical cord blood adiponectin, leptin as well as insulin and ghrelin levels in preterm and term infants, and elucidate the link between these hormones and fetal growth. Methods: A total of 149 mother-infant pairs (100 in the preterm group and 49 in the term group) were enrolled in the study. The preterm group was also divided into subgroups according to birth weight (≤1500g, 1501-2000g, 2001-2500g, 2500g), gestational age (＜34 weeks vs ≥ 34 weeks) and AGA/SGA. The general condition of mothers and the growth parameters of newborns at birth were recorded. Results: Adiponectin, leptin and ghrelin in the preterm group were lower than those in the term group (p＜0.05). In the preterm group, leptin of infants with gestational age ≥34 weeks was significantly higher than those with gestational age＜34 weeks(mean ln leptin: 0.632 vs 0.357 ng/ml, P=0.009).The adiponectin level in the SGA group was lower than that in the AGA group(mean ln adiponectin: 2.255 vs 2.840 ug/ml, P=0.001), while the ghrelin levels was higher than that in the AGA group(mean ln ghrelin: 6.292 vs 5.707 pg/ml, P<0.001). Leptin was significantly correlated with insulin in both preterm infants with BW> 2000g and term infants. Umbilical cord blood leptin was positively correlated with birth weight, length and head circumference of newborns (r = 0.460, 0.311, 0.310, all p<0.05), while ghrelin was negatively correlated with birth weight, length and head circumference of newborns(r=-0.372,-0.415,-0.373, all p＜0.05). Conclusions: Lack of proper acquisition of adipose tissue by the fetus in prematurity is associated with changes in the cord blood adiponectin, leptin and ghrelin levels. The dysregulation of those hormones in preterm infants may be a risk factor for fetal growth and future metabolic diseases.